2002
DOI: 10.1002/bit.10384
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the enzymatic kinetically controlled synthesis of cephalexin: Influence of diffusion limitation

Abstract: In this study the influence of diffusion limitation on enzymatic kinetically controlled cephalexin synthesis from phenylglycine amide and 7-aminodeacetoxycephalosporinic acid (7-ADCA) was investigated systematically. It was found that if diffusion limitation occurred, both the synthesis/hydrolysis ratio (S/H ratio) and the yield decreased, resulting in lower product and higher by-product concentrations. The effect of pH, enzyme loading, and temperature was investigated, their influence on the course of the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 23 publications
0
38
0
1
Order By: Relevance
“…Intrinsic enzyme kinetics Schroën et al 2002 derived kinetic equations for product and by-product formation using the King-Altman approach. Duggleby et al (1995) and Svedas et al (1980) found that the enzyme only binds PGA and 7-ADCA if the amino group is neutral (the carboxylic acid group can be Fig .…”
Section: Kineticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Intrinsic enzyme kinetics Schroën et al 2002 derived kinetic equations for product and by-product formation using the King-Altman approach. Duggleby et al (1995) and Svedas et al (1980) found that the enzyme only binds PGA and 7-ADCA if the amino group is neutral (the carboxylic acid group can be Fig .…”
Section: Kineticsmentioning
confidence: 99%
“…In the second, CEX is hydrolyzed to yield 7-ADCA and PG. Schroën et al (2002) showed that transport of multiple reactants limited each reaction differently. Overall, it was shown that diffusion limitations in Assemblase cause a reduced cephalexin production rate, a reduced yield on substrate, and an increased formation rate of the unwanted by-product PG in comparison with the free enzyme (Schroën et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations